1978
DOI: 10.1029/ja083ia06p02567
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic acceleration induced by convection in the plasma sheet

Abstract: A study of the average energy and temperature of ions precipitated in the nocturnal auroral zone during periods of low magnetic activity is presented. On the basis of this study, carried out using the Aureole 1 satellite, it can be concluded that the characteristics of ions at auroral altitudes well reflect their convection in the distant plasma sheet and the betatron and Fermi type acceleration accompanying it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…During the subsequent motion of the satellite toward the equator, the electron energy increases almost monotonically with decreasing latitude. This is a typical signature of the plasma acceleration by betatron and Fermi mechanisms in the central plasma sheet [ Galperin et al , 1978]. As in the previous case, the auroral zone shows a polar region (prior to ∼0638 UT) associated with electrons originating from the PSBL and an equatorial region connected to the CPS.…”
Section: Observationsmentioning
confidence: 57%
“…During the subsequent motion of the satellite toward the equator, the electron energy increases almost monotonically with decreasing latitude. This is a typical signature of the plasma acceleration by betatron and Fermi mechanisms in the central plasma sheet [ Galperin et al , 1978]. As in the previous case, the auroral zone shows a polar region (prior to ∼0638 UT) associated with electrons originating from the PSBL and an equatorial region connected to the CPS.…”
Section: Observationsmentioning
confidence: 57%
“…In this analysis we are less interested in the boundary than in looking at the ion characteristics as a function of latitude well removed from the boundary. As pointed out above, previous research has shown [Galpernin et al, 1976[Galpernin et al, , 1978Hultqvist, 1979;Sauvaud et al, 1981] that over a range of latitudes, for individual passes in the evening and morning sectors and during quiet times, the average energy of the precipitating ions varies with L shell approximately as would be expected if the ions were undergoing quasi-static, adiabatic compression.…”
Section: Eave(90 ø) = Eaveo(90ø)(lo/l) 3 (7)mentioning
confidence: 83%
“…Specifically, we will discuss the degree to which the variation in ion characteristics, at least over some range of latitudes, MLTs, and activities, is consistent with a simple physical model of adiabatic compression and the creation of Alfven layers as the ions are transported within the magnetosphere. The chief motivation for this is to determine the degree to which such adiabatic effects, reported by earlier researchers in case studies, are repeated in the average study [Hultqvist, 1974;Galpernin et al, 1976Galpernin et al, , 1978Hultqvist, 1979 , and references therein; Sauvaud et al, 1981]. In addition, we will consider the relationship of the precipitating ions to the various boundary regions in the magnetosphere, the implications of the variation of the average energy and integral number flux in the cusp region, and the degree to which the pattern of ion precipitation agrees with models for the motion of ions in the magnetosphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both plates, the results of the simulations were sorted according to pitch angle, namely, from 5 ø to 15 ø (left panels), from 30 ø to 60 ø (middle panels) and from 75 ø up to 85 ø (right panels). Distinct initial temperatures were considered in the two upper panels, and the case with two spectral maxima [e.g., Galperin et al, 1978;Lennartsson, 1992] is shown in the bottom panels.…”
Section: Postdipolarization Evolutionmentioning
confidence: 99%